PEMBERDAYAAN KELOMPOK TANI DALAM MENINGKATKAN HASIL PERTANIAN DI DESA ARJASARI KECAMATAN LEUWISARI KABUPATEN TASIKMALAYA - Malindir, Gaston Otto; Mashud, Aldi Budi (Jurnal Politik Pemerintahan Dharma Praja, 2022)
Empowerment of farmer groups is a series of activities carried out to improve the knowledge and skills of farmers through training and counseling in order to create independent and competitive farmers. The phenomenon found in the field is the lack of knowledge and skills of farmers in applying technological innovations and the incapacity of farmer groups resulting in the yield of production fluctuating or going up and down every harvest season. The purpose of this study is about empowering farmer groups by the Arjasari Village Government using empowerment theory with indicators of human development, business development, environmental development and institutional development. The research method used is descriptive qualitative with data collection techniques literature study and field studies through interviews and observations. The results of the study based on the four indicators did not run optimally because there were no capacity building efforts carried out by the Village Government either through training or counseling, while several obstacles to implementing farmer group empowerment were lack of attention, budget constraints, and weak partnership network development. The author gives advice to the Village Government to conduct training and counseling to farmer groups regularly and gradually in order to achieve independence and welfare of farmers. Keywords: Empowerment, Farmer Groups, Village Government